THE POLITICAL PARTICIPATION OF BEGINNING VOTERS IN PRESIDENTIAL ELECTIONS 2019 IN BEKASI - Muradi, .; Kartini, Dede Sri; Fathia, Vidya (Department of Government, FISIP, Universitas Padjadjaran, 2021)
This study aims to examine the attitude of beginner's political participation in simultaneous general elections in Bekasi City in 2019. The research method used in this study is quantitative. Data collection techniques using survey methods by distributing 100 questionnaires to two schools in the city of Bekasi and They are over 17 years. The technique used is purposive sampling. The data analysis technique used is descriptive statistics. The mean, mode, median, standard deviation, and minimum and maximum values of each response in each question are searched and analyzed with the software. The results of this study indicate that the political participation of novice voters in Bekasi City is not yet high. This can be seen from the forms of political participation used, they only focus on the general election of a president and vice president, but do not participate in political organizations, political parties, or protest actions against the government. In addition, the things that influence a person to be able to participate in elections are the profile of each candidate, the candidate's debates and the policies that will be taken when they are elected as future leaders. Furthermore, the most popular media by novice voters is social media.gb777